Study of Radioclinical and Risk Factors of Cerebral Venous Thrombosis: A Retrospective Analysis of Patients Presenting to a Tertiary Hospital in Mogadishu, Somalia - Adam BA; Osman AA; Sheikh Hassan M; Sidow NO; Osman Hidig MF; Mohamed AA; Ibrahim AA; Mohamed SA; Mohamed YG; Ahmed SA; Jeele MOO; Hassan MO (International Journal of General Medicine)
Bakar Ali Adam,1,2 Ahmed Adam Osman,3 Mohamed Sheikh Hassan,1,2 Nor Osman Sidow,1 Mohamed Farah Osman Hidig,1 Abdulkadir Ahmed Mohamed,1 Abdiwahid Ahmed Ibrahim,1 Said Abdi Mohamed,1 Yahye Garad Mohamed,3 Said Abdirahman Ahmed,4 Mohamed Osman Omar Jeele,5 Mohamed Omar Hassan4 1Department of Neurology, Mogadishu Somali Turkish Training and Research Hospital, Mogadishu, Somalia; 2Faculty of Medicine and Surgery, Mogadishu University, Mogadishu, Somalia; 3Department of Radiology, Mogadishu Somali Turkish Training and Research Hospital, Mogadishu, Somalia; 4Department of Cardiology, Mogadishu Somali Turkish Training and Research Hospital, Mogadishu, Somalia; 5Department of Internal Medicine, Mogadishu Somali Turkish Training and Research Hospital, Mogadishu, SomaliaCorrespondence: Bakar Ali Adam, Email atiika2009@gmail.comBackground: Cerebral venous thrombosis (CVT) is a rare but potentially life-threatening condition characterized by the formation of a blood clot in the dural venous sinuses or cerebral veins. CVT presents a diverse array of clinical symptoms, making its diagnosis challenging. Understanding regional variations and specific risk factors associated with CVT is crucial, especially in low-resource settings like Somalia, where epidemiological data is limited and healthcare resources are scarce.Objective: This study aims to investigate the clinical and risk factors associated with CVT in patients presenting to Mogadishu Somali-Turkey Recep Tayyip Erdogan Research and Training Hospital, a tertiary hospital in Mogadishu, Somalia.Methods: We conducted a retrospective observational study involving 68 patients diagnosed with CVT between January 2019 and December 2023. Data included demographic information, clinical presentations, risk factors, and anatomical thrombosis locations. Descriptive statistics and chi-square tests were used for analysis.Results: The majority of patients were female (86.76%) and aged 20– 40 years (86.76%). Significant risk factors included the postpartum period (77.94%) and pregnancy, with statistical analysis showing strong associations between CVT and the postpartum period (χ² = 62.96, p < 0.0001) and pregnancy (χ² = 5.21, p = 0.022). Postpartum CVT was linked to thrombosis location (p = 0.025). Headache was the predominant symptom (98.53%), followed by altered mental status (83.82%), focal motor deficits (80.88%), and seizures (70.59%). The superior sagittal sinus was the most commonly involved site (57.35%).Conclusion: This study emphasizes the postpartum period as a significant risk factor for CVT in Somalia and highlights the need for clinical vigilance and early intervention strategies. Larger, multicenter studies are needed to validate these findings.Keywords: cerebral venous thrombosis, CVT, postpartum, pregnancy, risk factors, Somalia, regional study